Antimycobacterial metabolites from Plectranthus. Royleanone derivatives against Mycobacterium tuberculosis strains - Rijo, Patrícia (2011)
The antimycobacterial activities of eight diterpenes, 1–8, isolated previously from Plectranthus and eleven esters, 9–19, of 7α-acetoxy-6β,12-dihydroxyabieta-8,12-diene-11,14-dione (5) were evaluated against the MTB strains H37Rv and MDR. Only diterpenoids with a quinone framework revealed anti-MTB activity. Abietane 5 and its 6,12-dibenzoyl, 12-methoxybenzoyl, 12-chlorobenzoyl, and 12-nitrobenzoyl esters, 9, 11, 12, and 13, respectively, showed potent activities against the MDR strain with MIC values between 3.12 and 0.39 μg/ml. Cytotoxic activities towards 3T3 and Vero cells were also evaluated. Compound 11, with the best selectivity index, may be a suitable lead for further chemical modifications. The complete structural elucidation of the new esters, 9–14, 16, 18, and 19, as well as the NMR data of known derivatives 15 and 17 are reported.